2014
DOI: 10.1002/smj.2286
|View full text |Cite
|
Sign up to set email alerts
|

How CEO hubris affects corporate social (ir)responsibility

Abstract: Grounded in the upper echelons perspective and stakeholder theory, this study establishes a link between CEO hubris and corporate social responsibility (CSR). We first develop the theoretical argument that CEO hubris is negatively related to a firm's socially responsible activities but positively related to its socially irresponsible activities. We then explore the boundary conditions of hubris effects and how these relationships are moderated by resource dependence mechanisms. With a longitudinal dataset of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
440
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 442 publications
(497 citation statements)
references
References 128 publications
(207 reference statements)
19
440
0
1
Order By: Relevance
“…This stream of work notes that the level of CSR efforts by firms is partly determined by the moral orientations of the individuals in influential positions [18][19][20]. More interestingly, some researchers suggested that the desires of the upper-echelon members of firms for more public attention, a better reputation, and higher labor market value are also important drivers behind their firms' pursuit of CSR initiatives [20,21]. While this line of work focuses on the attributes of individual firm decision-makers as an explanation for the CSR performance of firms, others moved their attention up to group-level features of the key decision-making body within firms.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…This stream of work notes that the level of CSR efforts by firms is partly determined by the moral orientations of the individuals in influential positions [18][19][20]. More interestingly, some researchers suggested that the desires of the upper-echelon members of firms for more public attention, a better reputation, and higher labor market value are also important drivers behind their firms' pursuit of CSR initiatives [20,21]. While this line of work focuses on the attributes of individual firm decision-makers as an explanation for the CSR performance of firms, others moved their attention up to group-level features of the key decision-making body within firms.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…When practical wisdom fails, why does it so, how, and in what conditions? What is the role of hubris (Takacs Haynes et al, 2015;Tang et al, 2015) as well as of narcissism and power structures (Stein, 2007(Stein, , 2013Kets de Vries, 2004) in contributing to such failure?…”
Section: Senior Managers Atmentioning
confidence: 99%
“…Tang et al (2015) claim to be the first to link CSR to managerial psychological bias. They find that CEO hubris is negatively associated with socially responsible investment but is positively associated with socially irresponsible investment.…”
Section: Ceo Overconfidence and Csrmentioning
confidence: 99%